Efl Students’ And Teachers’ Attitudes Towards Using Differentiated Instruction In Higher Education - Lombarkia, Soukeina; Guerza, Radia (جامعة الوادي - university of Eloued, 2021)
Abstract The present paper attempts to identify English as a Foreign Language (EFL) students’ and teachers’ attitudes towards using differentiated instruction in higher education, as an alternative teaching approach. It employed a descriptive method in the form of two questionnaires, randomly administered to forty (40) second-year students and fifteen (15) teachers at the department of English, Batna-2 University. Data were organized and analyzed through descriptive statistics. The findings reveal that both teachers and students have, to some extent, a positive tendency towards using differentiated instruction. With regard to learning obstacles, students call for alternative techniques to better understand the lesson. Typically, they prefer to learn within their cognitive capacities to get actively involved during the course. However, teachers accentuate various strategies that can be used in the classroom to achieve a differentiated learning atmosphere. They also support the use of differentiated lesson plans, varied activities, and flexible grouping, which are designed with reference to varied student learning traits. يرمي هذا البحث إلى تحديد مواقف طلبة وأساتذة اللغة الانجليزية تجاه استخدام منهج التعليم المتمايز في التعليم العالي، باعتباره مقاربة تعليمية بديلة. حيث تم استخدام خلاله المنهج الوصفي على شكل استبيانين، وزعا اعتباطيا على أربعين طالبا في السنة الثانية، بالإضافة إلى خمسة عشر أستاذا في قسم اللغة الانجليزية، جامعة باتنة-2. من ثم قمنا بتجميع البيانات وتحليلها من خلال إحصاء وصفي، حيث كشفت النتائج بأن لكل من الطلبة والأساتذة مواقف إيجابية، إلى حد ما، تجاه استخدام التدريس المتمايز. وبالأخذ بعين الاعتبار مشاكل التعلم، طالب الطلاب بإدراج تقنيات بديلة لفهم أفضل للدروس، كما عبروا عن تفضيلهم التعلم ضمن نطاق قدراتهم الإدراكية حتى يتسنى لهم المشاركة بشكل أكثر فعالية في الدروس. أما بالنسبة للأساتذة، فقد تطرقوا إلى العديد من الاستراتيجيات التي يمكن اللجوء إليها في القسم من أجل تحقيق جو التعليم المتمايز، كما أيدوا بشدة استخدام خطط دروس متمايزة، بالإضافة إلى تقسيم الطلاب إلى مجموعات بحسب سماتهم التعلمية.
مقال
Keywords: Differentiated instruction ; EFL students’ attitudes ; EFL teachers’ attitudes ; higher education